Racing Culture: Critical race theory, culture wars, anti/Blackness, and in/formal education in the 1990s - James-Gallaway, ArCasia D.; James-Gallaway, Chaddrick D. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
In this conceptual paper, we argue that many episodes of the so-called culture wars of the 1990s in the U.S. can be better understood as attacks on Blackness, a contention that critical race theory illuminates. To substantiate this claim, we recast key societal episodes through a Black perspective that unfolded in both formal and informal educational spaces. We demonstrate that the notion of the culture wars reflects a pivotal tension between Black, often gendered, modes of expression and dominant US culture, which we assert operates under the guise of morality. Drawing on critical race theory’s themes of racial realism, intersectionality, and counter storytelling, we analyze three racialized occasions often subsumed under the culture wars umbrella: the scapegoating of hip hop, specifically Sister Souljah, for systemic racism; Lani Guinier’s Assistant Attorney General nomination revocation; and the Oakland Ebonics Debate. To end, we illustrate the current relevance of these enduring culture wars themes in a hip hop-informed prison-based literacy initiative and the curricular prohibition of African American studies.